1979
DOI: 10.1152/ajprenal.1979.236.3.f246
|View full text |Cite
|
Sign up to set email alerts
|

Renal and nephron hemodynamics in spontaneously hypertensive rats

Abstract: Renal and nephron hemodynamics were compared between anesthetized, nondiuretic, spontaneously hypertensive rats (SHR) and Wistar-Kyoto rats (WKY). Although the mean arterial pressure was higher in SHR than in WKY, 158 VS. 114 mmHg, glomerular filtration rate (GFR) and renal blood flow (RBF) were similar in both groups. So were intrarenal hydrostatic pressures, single nephron GFR (SNGFR), and single nephron blood flow (SNBF). Accordingly, the increased renal vascular resistance (RVR) in SHR was due to predomina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
1

Year Published

1982
1982
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(103 citation statements)
references
References 0 publications
6
96
1
Order By: Relevance
“…6 -7 ' 20 The results of the present study indicate that the intermediate ILA segment exhibits an augmented myogenic response that may also contribute to the increased preglomerular resistance, especially of superficial glomeruli. It is tempting to speculate that the enhanced vasoconstriction of the intermediate ILA acts in concert with afferent arteriolar vasoconstriction to prevent or attenuate elevated glomerular capillary pressure in superficial nephrons.…”
Section: Altered Pressure Response Of the Interiobular Artery In Sponmentioning
confidence: 57%
See 1 more Smart Citation
“…6 -7 ' 20 The results of the present study indicate that the intermediate ILA segment exhibits an augmented myogenic response that may also contribute to the increased preglomerular resistance, especially of superficial glomeruli. It is tempting to speculate that the enhanced vasoconstriction of the intermediate ILA acts in concert with afferent arteriolar vasoconstriction to prevent or attenuate elevated glomerular capillary pressure in superficial nephrons.…”
Section: Altered Pressure Response Of the Interiobular Artery In Sponmentioning
confidence: 57%
“…2 We have previously demonstrated that myogenic afferent arteriolar vasoconstriction is reset to higher renal arterial pressure (RAP) levels in spontaneously hypertensive rats (SHR). 3 Although the afferent arteriole is primarily responsible for both acute 4 -5 and chronic 6 ' 7 adaptations to elevated RAP, the interlobular artery (ILA) may also contribute to renal autoregulation. 8 ' 9 The involvement of the ILA in chronic adaptations of the renal vasculature to hypertension has not been previously examined.…”
mentioning
confidence: 99%
“…Hemodynamic changes in the kidney, eg, increased vascular resistance, 15 during the development of hypertension might also contribute to altered oxygen tension in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 The increase in resistance appears to be more marked in the renal vasculature compared with the increase seen in other vascular beds. 29 As renal resistance resides predominantly within the afferent arterioles, 34 the increased renal resistance could be caused by narrowing of the afferent arteriolar lumen. Indeed, morphometric studies on the afferent arteriole of SHR and WKY have confirmed that afferent arteriolar diameters are smaller in SHR compared with WKY, whereas efferent arteriole diameters are comparable between the two strains.…”
Section: Role Of the Renal Microvascular Remodeling In The Pathogenesmentioning
confidence: 99%